Generation of a novel mouse strain with conditional, cell‐type specific, expression of DND1. Issue 11 (12th September 2019) - Nunez, Lisa; Mokkapati, Sharada; Yu, Chengtai; Deng, Jian M.; Behringer, Richard R.; Matin, Angabin
Summary: Dead‐End 1 (DND1) encodes an RNA binding protein critical for viable primordial germ cells in vertebrates. When introduced into cancer cell lines, DND1 suppresses cell proliferation and enhances apoptosis. However, the molecular function of mammalian wild‐type DND1 has mostly been studied in cell lines and not verified in the organism. To facilitate study of wild‐type DND1 function in mammalian systems, we generated a novel transgenic mouse line, LSL‐FM‐DND1 flox/+, which conditionally expresses genetically engineered, FLAG‐tagged and myc‐tagged DND1 in a cell type‐specific manner. We report that FLAG‐myc‐DND1 is indeed expressed in specific tissues of the mouse when LSL‐FM‐DND1 flox/+ is combined with mouse strains expressing Cre‐recombinase . LSL‐FM‐DND1 flox/+ mice are fertile with no overt health effects. We expressed FLAG‐myc‐DND1 in the pancreas and found that chronic, ectopic expression of FLAG‐myc‐DND1 led to increase in fasting glucose levels in older mice. Thus, this novel LSL‐FM‐DND1 flox/+ mouse strain will facilitate studies on the biological and molecular function of wild‐type DND1.